Vascular Access Site Complications Do Not Correlate With Large Sheath Diameter in TAVI Procedures With New Generation Devices - Gonska, Birgid; Reuter, Christopher; Mörike, Johannes; Rottbauer, Wolfgang; Buckert, Dominik (Frontiers in Cardiovascular Medicine, 2021)
Background: Vascular complications after transfemoral transcatheter aortic valve implantation (TAVI) are associated with morbidity and mortality. However, consistent predictors have not been identified yet. The size of the implantation sheath seems to play a role, though especially with new generation TAVI devices and their improved sheaths and delivery systems this remains uncertain. Objectives: This study aimed to determine the incidence and predictors of access site-related vascular complications (VC) in the era of new generation TAVI devices. Methods and Results: Four hundred consecutive patients receiving TAVI in an experienced tertiary care center were analyzed. VC occurred in 89 patients (22.25%) with the majority being minor VC (21%) and only 1.25% major VC. Possible predictors for VC were tested, and only peri-interventional dual antiplatelet therapy (DAPT) showed to be predictive for VC [OR 2.11 (95% CI 1.10–4.06, p = 0.025)]. The female gender [OR 0.75 (95% CI 0.44–1.3), p = 0.31], sheath to femoral artery ratio >1.05 [OR 1.18 (95% CI 0.66–2.08, p = 0.58)], calcification of the access site vessel [OR 0.83 (95% CI 0.48–1.42, p = 0.48)], known peripheral artery disease [OR 0.95 (95% CI 0.4–2.25, p = 0.9)], and BMI ≥ 25 kg/m2 [OR 0.69 (95% CI 0.41–1.19, p = 0–19)] were not predictive of VC. The larger sheath with 20 French even showed less VC than the smaller sheath with 16 French [OR 0.43 (95% CI 0.25–0.74, p = 0.002)]. Conclusions: Overall, the rate of major and minor VC was low in this study population (for major VC: rate of 1.25%). Predefined risk factors were not associated with the occurrence of VC, except for peri-interventional treatment with DAPT. Especially, larger sheath size could not be identified as a predictor for VC in the setting of TAVI procedures performed with contemporary devices.